(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2024)
The effect of ionizing radiation (electrons with E = 1.8 MeV, γ-quanta 60Со, X-ray emission with E≤100 keV) on the photoluminescence spectra and reflection spectra of CdZnTe / ZnTe quantum-size structures was investigated. For А2В6 quantum wells, degradation of photoluminescence takes place at much lower irradiation doses. The change in the profile of the wells as a result of irradiation was calculated with respect to shifts of photoluminescence peaks. The role of cadmium diffusion and internal stresses in radiation-induced degradation of quantum-size heterostructures is discussed.